Assessment Of Raw And Coagulated Latex Wastewater Of Enhance Aeration Stabilization Basin (Asb) A Batch Study - Shawal, Luqman Hakim (Universiti Sains Malaysia, 2019)
The study is a method of aeration treatment for raw latex wastewater produced by manufacturing product that originated from latex processing material devices companies in Kamunting, Taiping. Perak. Large quantities of raw latex wastewater which high in COD and BOD value causing serious water pollution. Raw latex wastewater is one of the industrial wastewater generated from manufacturing product that originated from latex processing material. There are three stages of wastewater treatment which is physical, chemical and biological treatment. In this study, only biological treatment was performed to treat latex wastewater and the efficiency of removal was compared between three condition aeration process. Aeration process divided into three different conditions which is aeration of wastewater, aeration of wastewater with bacteria and aeration of wastewater after coagulation. The hydraulic retention time (HRT) is fixed for the aeration process is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours and 24 hours respectively. The coagulation process used ferric chloride as a coagulant. All the treated effluent from the aeration of wastewater, aeration of wastewater with bacteria and aeration of wastewater after coagulation process was compared to the standard B discharge for industrial effluent.